2017
DOI: 10.1021/acschembio.7b00232
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modulation of Protein O-GlcNAcylation via OGT Inhibition Promotes Human Neural Cell Differentiation

Abstract: The enzymes that determine protein O-GlcNAcylation, O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA), act on key transcriptional and epigenetic regulators, and both are abundantly expressed in the brain. However, little is known about how alterations in O-GlcNAc cycling affect human embryonic stem cell (hESC) neural differentiation. Here, we studied the effects of perturbing O-GlcNAcylation during neural induction of hESCs using the metabolic inhibitor of OGT, peracetylated 5-thio-N-acetylglucosamine (Ac4-5SGl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 56 publications
7
46
0
Order By: Relevance
“…Notably, others have shown that Ac 4 5SGlcNAc ( 3 ‐OAc) appears to be able to inhibit other glycosyltransferases in cell lines . We found, however, by lectin blot assessment that 12 induced no apparent changes in other forms of protein glycosylation in all tissues tested (Figure S7) even at a dose of 300 mg kg −1 after 48 h, which is consistent with a recent report on the use of the parent compound Ac 4 5SGlcNAc ( 3 ‐OAc) in cells …”
Section: Figuresupporting
confidence: 91%
“…Notably, others have shown that Ac 4 5SGlcNAc ( 3 ‐OAc) appears to be able to inhibit other glycosyltransferases in cell lines . We found, however, by lectin blot assessment that 12 induced no apparent changes in other forms of protein glycosylation in all tissues tested (Figure S7) even at a dose of 300 mg kg −1 after 48 h, which is consistent with a recent report on the use of the parent compound Ac 4 5SGlcNAc ( 3 ‐OAc) in cells …”
Section: Figuresupporting
confidence: 91%
“…The hexosamine biosynthesis pathway (HBP) is a nutrient-sensing pathway that depends on glucose, glutamine, and cytosolic Ac-CoA levels (Figure 2 Conversely, a decrease in O-GlcNAcylation disrupts self-renewal and reprogramming (57), but promotes differentiation in neuronal cells (63)(64)(65). Moreover, CPTFs such as OCT4 and SOX2 harbor an O-GlcNAcylation motif that is quickly erased upon differentiation (57).…”
Section: Hexosamine Biosynthesis and Fate Transitionsmentioning
confidence: 99%
“…Total O-GlcNAc in brain homogenate is the highest during pre- and perinatal development and decreases during later development (Yanagisawa and Yu 2009 ; Liu et al 2012 ). In vitro , early neuronal differentiation also has been associated with a decrease in global O-GlcNAcylation, albeit the global O-GlcNAc levels appear to cycle from day to day (Andres et al 2017 ; Speakman et al 2014 ). At around one month after birth, overall O-GlcNAc plateaus at a relatively low level and then remains stable for most of adulthood (Liu et al 2012 ).…”
Section: O-glcnac and Its Regulation In The Nervous Systemmentioning
confidence: 99%
“…Overall OGT protein levels and activity in vivo are mostly stable during development through adulthood (Yanagisawa and Yu 2009 ; Liu et al 2012 ). Neuronal differentiation in vitro , in contrast, has been associated with a small decrease in OGT mRNA and protein abundance (Andres et al 2017 ; Maury et al 2013 ). In the very old brain, the total protein level may go down slightly (Fulop et al 2008 ).…”
Section: O-glcnac and Its Regulation In The Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation